Role of diapause in dispersal and invasion success by aquatic invertebrates - Nicoletta RICCARDI (Journal of Limnology, 2004)
Review of existing literature shows an important role of diapause in dispersal of aquatic invertebrates. There is evidence that among aquatic invertebrates, the role of diapause in dispersal can be important in crustaceans, specifically for species that produce resting eggs. Analysis of dispersal vectors of diapausing species revealed the increasing role of human-mediated vectors of species dispersal during last century (intentional and unintentional introductions, specifically associated with shipping) in comparison with natural vectors (currents, wind, birds). Generally, the role of human-mediated vectors is most important for species dispersal across geographical barriers and into large aquatic ecosystems affected by shipping. Current human-mediated transport vectors increase rates of aquatic species introductions in many orders of magnitude in comparison with historical nature-driven species dispersal rates. Ability to develop diapausing resting stages facilitates species survival during movement across geographical barriers under extreme conditions, such as in ballast tanks of ships. Case studies for invasive species of Cladocera show that some invaders may possess adaptive life cycles, switching to the early prolonged gamogenetic reproduction, which facilitates their invasion success into novel ecosystems and further dispersal by both natural and human-mediated vectors.